Preparation before games and adjustment for each play in American Football - Itai, M. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In America football, it is asserted that preparations before games are the crucial key to the winning games much more than in any other footballs. It is brought about by the characteristics proper to American football that all the plays, sixty or more in a game, are "set play" and without some unintended "turnovers", both team would be given almost the same number of opportunities of offence. Accordingly, on the theoretical level, preparations to find out the opponents discrepancy and to shore up those of our team are inexorable. However, theoretical formulations and tangible games are thoroughly different two issues as in the other footballs. I would point out the crucial key in the preparations and adjustment in each game as follows. Methods In this paper, I would take some uncertain matter in games and in the actual manner of the players, and then argue how we cope with them, mainly on the offensive standpoint to shed light on the topic referred above. Results & Discussion It goes without saying that preparations according to the opponent defense before games are unavoidable. In fact it is decisive for the team to pursue completion in each play through practice before games. At the same time, in the games, coaches should vary play calls elastically on accordance with the players` physical/mental conditions and the field conditions. It is the fundamental for coaches to realize the players` physical/mental conditions so that they may make right calls. Conclusion Even though a play call should be perfect, it is of no use to winning games if players can not carry it out. As a result, I would elucidate that to realize the players` physical/mental conditions is much more momentous than any other issues as play calls.